Conoscere la popolazione. Prevenzione, felicità e ordine sociale in Inghilterra (1798-1838) - Bonasera, Jacopo (Studi Politici, 2025)
This essay analyses the contributions of two early proponents of birth control in England – Francis Place and Richard Carlile – in order to highlight the theoretical and political consequences of the adoption of the Malthusian “principle of population” within a progressive, radical and cooperative vision of politics. Starting from the intertwining of prevention, happiness and social order present in both Malthus’s writings and those of his early utilitarian readers, the aim is to highlight the historical and conceptual shift – along with some key theoretical continuities – to which “Malthusianism” subjects Malthusian thought. For Malthus, it is the “preventive” restraint of sexual passion that is “moral”; in arguing for the introduction of contraceptives, Place and Carlile affirm the “natural” character of the principle of population, but see in it the possibility of opening up the space for harmonious cooperation between rulers and ruled. In this way, ‘knowing’ the population becomes a prerequisite for the success of a reform of the established political and social order.